[Amendment to fire safety bill] (Tufts Archival Research Center, 2007)
Marginalia; Memorandum from Karen L.. Fernicola to Susan Stuntz and Martin Gleason regarding amendments made to the Moakley-Boucher bill on cigarette regulations. Lists the two changes made and how they affect the tobacco industry and attaches a copy of the new bill.